2021
DOI: 10.3389/fpls.2021.619158
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of the Gibberellin 2-oxidase Gene Family in Peach

Abstract: Peach (Prunus persica L. Batsch) trees grow vigorously and are subject to intense pruning during orchard cultivation. Reducing the levels of endogenous gibberellins (GAs) represents an effective method for controlling branch growth. Gibberellin 2-oxidases (GA2oxs) deactivate bioactive GAs, but little is known about the GA2ox gene family in peach. In this study, we identified seven PpGA2ox genes in the peach genome, which were clustered into three subgroups: C19-GA2ox-I, C19-GA2ox-II, and C20-GA2ox-I. Overexpre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 43 publications
1
24
0
Order By: Relevance
“…Gibberellin 2-oxidases (GA2oxs) are important GA metabolism enzymes that reduce the GA content [ 35 , 36 , 37 ]. In this work, the expression level of GA2ox1 was upregulated in the mtn1 mutant.…”
Section: Discussionmentioning
confidence: 99%
“…Gibberellin 2-oxidases (GA2oxs) are important GA metabolism enzymes that reduce the GA content [ 35 , 36 , 37 ]. In this work, the expression level of GA2ox1 was upregulated in the mtn1 mutant.…”
Section: Discussionmentioning
confidence: 99%
“…Editing PROCERA / SlDELLA in tomato and MaGA20ox2 in Musa acuminate (banana) using CRISPR-Cas9 results in shortened internodes (a dominant mutation and a loss-of-function mutation; Tomlinson et al., 2019 ; Shao et al., 2020 ). Overexpression of PsGA3ox1 and PpGA2ox1 lead to longer and more compact internodes in pea and Nicotiana tabacum (tobacco), respectively ( Reinecke et al., 2013 ; Cheng et al., 2021 ). GAs and PAC application also obviously change the internode length of two commercial grapevine cultivars ( Acheampong et al., 2015 ).…”
Section: Vegetative Growthmentioning
confidence: 99%
“…All of the genes discussed above ( Cla015407 , TIE1 , NHM1 , MaGA20ox2 , PsGA3ox1 , and PROCERA ) are classified into GA synthesis or signal genes directly influencing endogenous GA in tissues, and abnormal concentrations of endogenous GAs affect development of tissues, such as stem. We assume that this is also a conservative mechanism of horticultural species as in model plants where GAs positively regulate stem elongation ( Tomlinson et al., 2019 ; Shao et al., 2020 ; Cheng et al., 2021 ; Kou et al., 2021 ; Liu et al., 2022 ). Internode/stem is made up of millions of cells, and cell fate determines internode elongation.…”
Section: Vegetative Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…GA is the primary growth-promoting hormone of peach annual shoots, but the genes involved in biosynthesis and degradation are poorly understood. To properly regulate the growth of annual shoots, it is necessary to identify the genes that encode the enzymes that synthesize and deactivate GA. Our previous study identified seven PpGA2ox genes in peach [16]. The present study identifies the GA biosynthetic genes and analyzes their transcription levels as well as those of the deactivating PpGA2oxs in six internodes from the top to the bottom of peach shoots.…”
Section: Introductionmentioning
confidence: 96%